Shedding light on the clinical recognition process of transient global amnesia. (22nd June 2020) - Hoyer, C.; Ebert, A.; Pooyeh, A.; Eisele, P.; Gass, A.; Platten, M.; Szabo, K.
Abstract : Background and purpose: Diagnostic uncertainty is common in the emergency evaluation of neurological conditions such as acute confusional states, particularly for non‐neurologists. We aimed to investigate the clinical recognition process of transient global amnesia (TGA) before arrival at the hospital and in the emergency department (ED). Methods: In this retrospective observational study, medical records of 365 patients with TGA were analysed concerning mode of arrival, symptoms and suspected diagnosis made by pre‐hospital medical care providers and the ED neurologist. Results: More than half of the 248 patients who were evaluated before arrival at the hospital ( N  = 157, 63.3%) received a diagnosis of suspected stroke, whereas TGA was considered in only 16 patients (6.5%), with recognition of acute amnesia in 150 patients (60.5%) and disturbed orientation in 86 patients (34.7%). Repetitive questions by the patient were noted in 28 patients (11.3%). In contrast, in 355 patients (97.3%), TGA was considered the primary diagnosis by the ED neurologist. Diagnosis in the ED was achieved by documenting ongoing impairment of episodic verbal memory (100.0%), repetitive questions as a prominent ancillary finding (95.5%) and the lack of focal neurological symptoms (100.0%) or by carefully obtaining collateral history suggestive of anterograde memory disturbance (89.9%) and/or repetitive questions (85.7%). Conclusion: Recognizing TGA crucially depends on identifying isolated anterograde episodic long‐term memory disturbance or its observable effects such as repetitive questions and actions.